2021
DOI: 10.1016/j.biopha.2021.111469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renin-angiotensin system inhibitors on mortality during the COVID Pandemic among STEMI patients undergoing mechanical reperfusion: Insight from an international STEMI registry

Abstract: Background Concerns have been raised on a potential interaction between renin-angiotensin system inhibitors (RASI) and the susceptibility to coronavirus disease 2019 (COVID-19). No data have been so far reported on the prognostic impact of RASI in patients suffering from ST-elevation myocardial infarction (STEMI) during COVID-19 pandemic, which was the aim of the present study. Methods STEMI patients treated with primary percutaneous coronary intervention (PPCI) and enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Furthermore, in-hospital RASI treatment was associated with a significantly lower mortality, consistently in 2019 and 2020, without affecting the prevalence of SARSCoV2 infection. Therefore, confirming our previous report in a general population, [49] the present study confirms the overall mortality benefits of RASI among diabetic patients with STEMI. Moreover, it does not suggest a link between RASI therapy and COVID-19 susceptibility or subsequent worse outcomes among these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in-hospital RASI treatment was associated with a significantly lower mortality, consistently in 2019 and 2020, without affecting the prevalence of SARSCoV2 infection. Therefore, confirming our previous report in a general population, [49] the present study confirms the overall mortality benefits of RASI among diabetic patients with STEMI. Moreover, it does not suggest a link between RASI therapy and COVID-19 susceptibility or subsequent worse outcomes among these patients.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the risk of discontinuing ACEI/ARB is worrying since may decompensate patients with hypertension, chronic heart failure, chronic kidney disease and CAD. Furthermore, an analysis of a multicenter cohort showed that chronic ACEI/ARB use was associated with significantly lower mortality in patients with ST-elevation myocardial infarction during the COVID-19 pandemic [ 14 ]. Evidence of ACEI/ARB benefits is consistent [ 15 ] and could be superior to the risk of continuing it in COVID-19 acute setting.…”
Section: Introductionmentioning
confidence: 99%